2017
DOI: 10.6018/analesbio.39.22
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungus influence maize root growth and architecture in rock phosphate amended tropical soil

Abstract: Influencia del hongo arbuscular micorrícico en el crecimiento y arquitectura radicular en suelo tropical modificado con fosforitaHemos ensayado la influencia del homgo micorrícizo arbuscular (AM) Scutellospora calospora en la estructura, crecimiento, asimilación de nutrientes, actividad fosfatasa y dependencia micorrizal de raíces de maíz por adicción de 0-5% de fosforita (RP) en suelos deficientes de fósforo (P). La adicción de RP aumentó significativamente la longitud total de la raíz, el número de raíces a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In adverse environmental conditions, the AMF contributed to the increasing tolerance to abiotic and biotic stresses by their osmotic regulation and alleviation of oxidative stress [17,18,20]. Mechanisms of mycorrhizal plant tolerance to abiotic stresses, for instance, salinity, drought, as well as pollution, have critically been revised elsewhere [13,[21][22][23]. Despite the ubiquity of AMF in different harsh environmental conditions and their promising findings in protecting plants from stresses, few works have been undertaken to investigate the potential effects of AMF in fighting against salt stress in date palm [11,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In adverse environmental conditions, the AMF contributed to the increasing tolerance to abiotic and biotic stresses by their osmotic regulation and alleviation of oxidative stress [17,18,20]. Mechanisms of mycorrhizal plant tolerance to abiotic stresses, for instance, salinity, drought, as well as pollution, have critically been revised elsewhere [13,[21][22][23]. Despite the ubiquity of AMF in different harsh environmental conditions and their promising findings in protecting plants from stresses, few works have been undertaken to investigate the potential effects of AMF in fighting against salt stress in date palm [11,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the results showed that the highest available nutrient content was achieved with plants treated with (M + RP), followed by treatment with AMF only (M). In the same line, Priyadharsini and Muthukumar (2017) reported that AMF could improve the P availability in soil treated with RP. AMF improve the capability of host plants to obtain nutrients from the soil (Entry, Rygiewicz, Watrud, & Donnelly, 2002; Javaid, 2009).…”
Section: Resultsmentioning
confidence: 85%
“…Similarly, Duponnois, Colombet, Hien, and Thioulouse (2005) showed that the addition of combined AMF and RP to the soil leads to improved all plant growth than the individual addition. In the same line, Priyadharsini and Muthukumar (2017) reported that the maize growth significantly enhanced with AMF + RP addition.…”
Section: Resultsmentioning
confidence: 87%
“…In addition, AMF up-regulated mycorrhiza-specific P transporter genes to promote the P absorption by cells (Amijee et al, 1989). The mycorrhizal extraradical hyphae directly secretes phosphatase and indirectly promotes the root system to secrete organic acid to hydrolyze organophosphorus to inorganic phosphorus, all of these ways promote the uptake of P by plants (Duan et al, 2015;Perumalsamy et al, 2017).…”
Section: Changes In Leaf Glucose Fructose and Sucrose Contentsmentioning
confidence: 99%